Scholastic encyclopedia of the presidents and their times - Rubel, David; Scholastic Inc. (New York : Scholastic, 2009)
Provides a year-by-year account of the tenure of each U.S. president from the inauguration of George Washington to the events of the 2008 election season, providing information about the key issues, headlines, notable people, and fads for every year served, and includes a table of election results for all presidential elections, and a history of the White House.
Includes index.
6.8
3-6
Keywords: Presidents -- United States -- Encyclopedias, Juvenile; Presidents -- United States -- Encyclopedias; Presidents -- United States -- Encyclopedias; Presidents -- United States -- Biography; United States -- History -- Encyclopedias, Juvenile; United States -- Politics and government -- Encyclopedias, Juvenile; United States -- History -- Encyclopedias; United States -- Politics and government -- Encyclopedias; United States -- History -- Encyclopedias; United States -- Politics and government -- Encyclopedias